PERAN DEKSTROSA HIPERTONIK DALAM TATALAKSANA PROLOTERAPI UNTUK OSTEOARTRITIS LUTUT - Sekplin A. S. Sekeon; Sarita Sharchis (Jurnal Sinaps, 2019)
Osteoarthritis (OA) is a degenerative joint disease that involves damage to cartilage and surrounding tissue. In addition to damage and loss of articular cartilage, there is subarticular bone damage, osteophyte formation, ligament weakness, weakening of the periarticular muscles and, in some cases, synovial inflammation. Management of osteoarthritis consist of both pharmacological and non-pharmacological. Pharmacological treatments consist of invasive and non-invasive modalities. One of the most effective invasive therapies is prolotheraphy. Prolotheraphy is one of the treatment options for musculoskeletal injuries, including knee osteoarthritis